Impact of Pharmacists’ Counseling in Patients’ Knowledge of Warfarin in a Tertiary Care Cardiac Centre: A Prospective Randomized Controlled Study - Shrestha, Sweta; Bhattarai, Basudev; Ghimire, Avisek; Karmacharya, Yogesh; Khanal, Saugat; Shahukhal, Suman (Indian Journal of Pharmacy Practice)
Background: Warfarin is the mainstay of anticoagulation therapy; however, its’ use has been associated with many complications especially bleeding. Adequate patients’ knowledge on warfarin can improve anticoagulation control with reduction in adverse drug reactions and other associated complications. The objective of the study was to assess the impact of pharmacist’s counseling on patient’s knowledge of warfarin. Methods: A prospective randomized controlled study was carried out in Shahid Gangalal National Heart Center, Kathmandu, Nepal. A simple random sampling technique was used to enroll the participants in the intervention and control groups. A total of 99 patients participated in the study. Both the groups were administered the same questionnaire to assess their baseline knowledge. Verbal counseling of 20 min was provided to the intervention group whereas the control group received no pharmacist intervention. Final assessment of the knowledge level of both groups was done after a period of 2 months using the same questionnaire. Results: A significant increment in percentage of patients with adequate knowledge on warfarin was found in the counseled group after intervention (p<0.05). The results further suggested that significantly increased proportion of patients in the intervention group achieved a better control of INR (International Normalized Ratio) after the intervention. No significant association was found between duration of therapy, gender, age and the knowledge score of the patients. Conclusion: Pharmacist provided counseling can significantly improve patients’ knowledge on warfarin.
Keywords: Anticoagulation; Counseling; INR; Knowledge; Warfarin.